Karantina Tumbuhan di Indonesia dalam Masa Perdagangan Bebas - Nursamsi Pusposendjojo (Jurnal Perlindungan Tanaman Indonesia, 2005)
Plant quarantine is enacted to keep out foreign plant pests and to protect food, horticulture and estate crops from alien pests. The act prohibits or restricts entry into or passage through a country from foreign countries of plants, plant products, soil, and other materials carrying or likely to carry pests not known· to be established in the country. Experienced inspectors stationed at all points of entry into the country enforce quarantine of produce likely to introduce new pests. The importance of plant quarantine becomes more and more significant in the free trade era. Indonesia to be one of potential market for many agricultural products has still very limited number of plant quarantine inspectors. Number and quality of plant quarantine inspectors are badly needed in order enable coping the problems. Education and training should be organized and it is important to include plant quarantine in the Faculty of Agriculture curriculum.